PENGARUH STOCKMISPRICING TERHADAP RETURN REVERSAL PADA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rindy Permatasari (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at analyzing the effect of stock mispricing on the return reversal in size of company and book-to-market as controlling variable in share registered in Indonesian Stock Exchange in 2012-2016. The population of this research are all companies registered in Indonesian Stock Exchange in 2012-2016. The sample of the research are 148 companies selected through purposive sampling. The data were collected through documentation and examined with multiple linear regression using EVIEWS 9 program. The research showed that mispricing level had positive and significant effect on return reversal at the time of first week regression after the period of mispricing. In the second, third, and fourth week. The share had followed the process of mean pricing, which means that the return gradually went back to the appropriate return.Keyword:Mispricing, Return Reversal, Size, Book-to-Market